Inducing Behavioral Adaptations within web services gaining control over dynamic changes in web services. - Kulkarni, Naveen
Web services have evolved from plain application-integration enablers to value-added stand-alone functionality providers such as getting a quote to a comprehensive business function like processing orders. Enterprises are exploiting this new revenue model by offering such business functions as services on usage basis. Information sharing instances such as Amazon's e-commerce services have helped in the creation of new powerful solutions using business functions as services.